1998
DOI: 10.1364/ao.37.004806
|View full text |Cite
|
Sign up to set email alerts
|

Application of Zeeman modulation Faraday spectroscopy to the measurement of a magnetic field

Abstract: We report what is to our knowledge the first possibility of a NO(2) molecular magnetometer based on the Zeeman modulation magnetic rotation spectroscopic (ZM MRS) technique and the magneto-optic activity of NO(2). The linear dependence of the ZM MRS signal intensity on the modulating magnetic field is theoretically analyzed and experimentally measured. The design concept of the magnetometer and its main features are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The whole absorption cell was placed in a longitudinal dc magnetic field (Faraday configuration) with intensity of 300 gauss, and a pair of nearly crossed polarizers was located to each end of the absorption cell. The intensity of spectral lines of paramagnetic molecular ions could be enhanced in linearity significantly by the magnetic field [14]. An avalanche photodiode (APD) detector converted the light signal to an electronic one, and its output was demodulated by a double balanced mixer (DBM) at 480 MHz and by a lock-in amplifier at the discharge frequency of 37 kHz in sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The whole absorption cell was placed in a longitudinal dc magnetic field (Faraday configuration) with intensity of 300 gauss, and a pair of nearly crossed polarizers was located to each end of the absorption cell. The intensity of spectral lines of paramagnetic molecular ions could be enhanced in linearity significantly by the magnetic field [14]. An avalanche photodiode (APD) detector converted the light signal to an electronic one, and its output was demodulated by a double balanced mixer (DBM) at 480 MHz and by a lock-in amplifier at the discharge frequency of 37 kHz in sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The finding was that the intensity of the N 2 + electronic spectra increased with increasing magnetic field strength, in agreement with previously observed behavior of the magnetic rotation effect for neutral paramagnetic species. In this particular case, however, there was another possible explanation for the enhancement, viz. that the magnetic field confines the electrons, increasing the plasma density. , However, Luo et al have shown that this confining effect results in only a small increase in sensitivity. Regardless of which mechanism made the biggest contribution to the signal increase, there was almost a 4-fold increase in S/N over the range from 100 to 500 G. This is a promising development for velocity modulation spectroscopy using intense laser sources with large background drifts.…”
Section: 4 Oh-mr-vmsmentioning
confidence: 99%
“…that the magnetic field confines the electrons, increasing the plasma density. 16,47 However, Luo et al 16 have shown that this confining effect results in only a small increase in sensitivity. Regardless of which mechanism made the biggest contribution to the signal increase, there was almost a 4-fold increase in S/N over the range from 100 to 500 G. This is a promising development for velocity modulation spectroscopy using intense laser sources with large background drifts.…”
Section: Oh-mr-vmsmentioning
confidence: 99%
“…1, the spectral lineshapes are fourth derivatives of Gaussian profiles [17]. The spectrum of paramagnetic species can be linearly enhanced by the applied longitudinal magnetic field at low field limit [20], and the distinctive spectral phase characteristic [21] of Faraday rotation is helpful. The program 'Peakfit' has been used to decompose the overlapped spectral lines in order to determine their center wavelengths accurately.…”
mentioning
confidence: 99%